If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 22 = 13x + -62 Reorder the terms: 22 + 6x = 13x + -62 Reorder the terms: 22 + 6x = -62 + 13x Solving 22 + 6x = -62 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 22 + 6x + -13x = -62 + 13x + -13x Combine like terms: 6x + -13x = -7x 22 + -7x = -62 + 13x + -13x Combine like terms: 13x + -13x = 0 22 + -7x = -62 + 0 22 + -7x = -62 Add '-22' to each side of the equation. 22 + -22 + -7x = -62 + -22 Combine like terms: 22 + -22 = 0 0 + -7x = -62 + -22 -7x = -62 + -22 Combine like terms: -62 + -22 = -84 -7x = -84 Divide each side by '-7'. x = 12 Simplifying x = 12
| 3(2x-1)+2=2(x+3)-1 | | 5dx+6=2x-3 | | (X-3)+5=4(2x-5) | | 4-2(3-x)=7-x | | 7x-3=8+2x | | 5x-2=8x+7 | | b^2+b-9=0 | | -3x-8=4x-15 | | 1=4x+13 | | 6x-95=55 | | -z=-38 | | 8(3-x)=16 | | -9=11z | | p=3g+3w | | 8=k+20 | | -x+18=83 | | (2a-1)(a-3)=0 | | k^2-3k+2=0 | | 2k^2+4k-48=0 | | 36x^2-8=28 | | 81p^2+3=84 | | (3n^2-4n+1)-(8n^2-4n+17)=0 | | 25x^2+4=29 | | 9v^2-2=79 | | 3x^2-10x=5 | | (m-7m-11)=(m-8) | | 12-5=h+6 | | n^2-2n-24=0 | | -9(3u-8v+6w)= | | 4-(-17)= | | 18+[-7+(-9)]= | | 3k=k+18 |